Allelic Variation in Loci for Adaptive Response and Its Effect on Agronomical Traits in Chinese Wheat (Triticum aestivum L.) - Li-feng GAO; Pan LIU; Yan-chun GU; Ji-zeng JIA (Journal of Integrative Agriculture, 2014)
Heading date was an important trait that decided the adaptation of wheat to environments. It was modified by genes involved in vernalization response, photoperiod response and development rate. In this study, four loci Xgwm261, Xgwm219, Xbarc23 and Ppd-D1 which were previously reported related to heading time were analyzed based on three groups of wheat including landraces (L), varieties bred before 1983 (B82) and after 1983 (A83) collected from Chinese wheat growing areas. Generally, heading date of landrace was longer than that of varieties. Significant differences in the heading time existed within the groups, which implied that diversification selection was much helpful for adaptation in each wheat zone. Photoperiod insensitive allele Ppd-D1a was the first choice for both landrace and modern varieties, which promoted the heading date about four days earlier than that of sensitive allele Ppd-D1b. The three SSR loci had different characters in the three groups. Predominant allele combination for each zone was predicted for wheat group L and A83, which made great contribution to advantageous traits. Xgwm219 was found to be significantly associated with heading date in Yellow and Huai River Winter Wheat Zone (Zone II) and spike length in Middle and lower Yangtze Valley Winter Wheat Zone (Zone III), which implied functional diversification for adaption. Variation for earliness genes provided here will be helpful for whet breeding in future climatic change.